Production and assessment of microalgal liquid fertilizer for the enhanced growth of four crop plants. (September 2020) - Deepika, P.; MubarakAli, D.
Abstract: The microalgal biomass is widely used in various fields such as food, agriculture, energy, and so on. Due to the adverse effects of the chemical fertilizer, a demand arises for biofertilizer in order to preserve the soil, plants, and also the environment. Microalgae play an essential role in the field of agriculture where it is used as biofertilizers, as they are capable of fixing atmospheric nitrogen and convert it into ammonia for the growth of plants and also to stabilize soils. In this present study, algal liquid fertilizer was prepared and applied at three different doses to the four crop plants, Cucumis sativus, Solanum lycopersicum, Capsicum annuum, and Vigna radiata at various concentrations (0–100%). The application of the algal liquid fertilizer for the crop plants was a lead substitute for the commercially available chemical fertilizers, and also it is cost-effective. At low concentration (20%) of ALF showed maximum growth in all four crop plants. The growth parameters such as root and shoot length, number of leaves, and number of lateral roots were also recorded maximum at 20%. Biochemicals and growth parameters are supported by the data obtained. Graphical abstract: Image 1